Peran Pelatihan Self-Esteem Enhancement dalam Meningkatkan Resiliensi pada Residen di Yayasan “X” Sentul - Ignatia Susana Andreana Beryo Koba; O. Irene Prameswari Edwina; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2019)
The purpose of this research is to examine the effect of Self-Esteem Enhancement training on the increase of resilience of patients in “X” Foundation Sentul. Samples in this research are 7 patients who undergoing the addiction rehabilitation program and have experienced relapse. The data was collected using resilience questionnaire modified by the researcher, based on Bonnie Benard theory of Resilience (2004). The validation process used for resilience questionnaire was content validity. Degree of self-esteem was measured with Multidimensional Self-Esteem Inventory adapted from the original version of MSEI (O’Brien & Epstein, 1988). The quantitative data collected in this research was analysed using Wilcoxon Test. The result shows that there is significant increase in degree of resilience of patients in “X” Foundation after participating in the Self-Esteem Enhancement Training. Theoretical suggestion for further research is to conduct a thorough investigation on the impact of the increase of self-esteem on the aspects of resilience. The advice for “X” Foundation is to train the staffs and helpers to use the cognitive restructuring and problem solving skills in order to help the patients to increase their self-esteem and resilience. Keywords: resiliency, risk factors, self-esteem, self-esteem enhancement training, substance abuse